2005
DOI: 10.1159/000088919
|View full text |Cite
|
Sign up to set email alerts
|

Is Alexithymia Related to Negative Symptoms of Schizophrenia?

Abstract: Background: Alexithymic features are close to anhedonia, blunted affect, and alogia that are also characteristics of the negative symptoms of schizophrenia. This study aimed to evaluate whether alexithymia is associated with negative symptoms and is related to the change of schizophrenic symptoms over time. Sampling and Methods: A consecutive sample of 29 schizophrenic outpatients was evaluated at baseline and at 3, 6, and 12 months during appropriate treatment. They completed the Positive and Negative Syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 43 publications
3
27
0
3
Order By: Relevance
“…This could mainly be due to the fact that alexithymia in pregnant women remains an understudied topic. In addition, several studies showed that there was no significant relationship between alexithymia and the negative general symptoms [22,23]. Future prospective research is needed to explore the association between alexithymia and the development of mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…This could mainly be due to the fact that alexithymia in pregnant women remains an understudied topic. In addition, several studies showed that there was no significant relationship between alexithymia and the negative general symptoms [22,23]. Future prospective research is needed to explore the association between alexithymia and the development of mental illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Maggini and Raballo [19] have shown that difficulty identifying feelings was positively correlated with the positive syndromes (especially delusions) of schizophrenia, while van’t Wout et al [20] have reported that it was correlated with the negative symptoms. Todarello et al [21], however, found no correlation between alexithymia and the positive or negative syndromes of schizophrenia. The inconclusive results might be due to the heterogeneity of schizophrenia, which includes several other forms than the most common paranoid type [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The inconclusive results might be due to the heterogeneity of schizophrenia, which includes several other forms than the most common paranoid type [22,23]. Indeed, in the abovementioned studies, scholars had included various forms of schizophrenia [19,20,21], and even schizoaffective disorder [20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Theses authors has determined that the level of alexithymia in schizophrenia is characterized by affective flattening and poor of speech and other symptoms. However, other authors [2] deny this relationship. Theses authors examined the level of alexithymia in 29 patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 98%
“…Secondary alexithymia has a psycho-emotional nature, the main reason is disorder of interaction with mother on the first year of life. Literary sources reveals a high level of alexithymia in the neuroses and psychosomatic disorders [2,3]. Sung hwa Son et al [4] had studied the level of alexithymia in depression, somatoform, anxiety and psychotic disorders among Koreans.…”
Section: Introductionmentioning
confidence: 99%